Cultural and Environment-Based Integrated Tourism Development Assistance Program at Tegalinggah Cliff Temple, Gianyar, Bali - Saputra, Roy; Nita Loktika, Nengah; Maharta Fujiasa, I Gede (Riwayat: Educational Journal of History and Humanities, 2024)
This study aims to analyze the Integrated Tourism Development Assistance Program Based on Culture and Environment at Tebing Tegalinggah Temple, focusing on empowering local communities and preserving the environment and culture. A descriptive qualitative approach was used by collecting data through in-depth interviews, participatory observation, and documentation. The results show that the assistance program successfully increased active community participation in tourism management, environmental conservation, and cultural promotion. The program also had a positive impact on the local economy, particularly by increasing income from the tourism sector and empowering women and youth groups. Challenges include limited infrastructure and the need to strengthen tourism promotion strategies. Additionally, there are opportunities to develop ecotourism and educational tourism as part of sustainable tourism management. Therefore, this assistance program can serve as a model for integrated tourism development based on culture and environment in other regions.